The Effect of Local Own Source Revenue, Tax Effort, and Capital Expenditure on The Level of Regional Financial Independence (Study on District/City Government in West Java Province Period 2019-2021) - Andini Nur Oktavianti; Hani Sri Mulyani; Yogi Ginanjar; Agustine Sulviani; Dadang Suhendar (Finance and Business Management Journal, 2023)
This study aimed to investigate the effect of regionally sourced income, tax effort, and capital expenditure on the level of regional financial independence at the provincial city/district government. West Java from 2019 to 2021. The population of this study consisted of districts/cities in West Java province, totaling 27 districts/cities, using the saturation sampling method with a total sample of 81. sample. The analytical methods used are descriptive and test analysis, classical hypothesis testing, analysis and coefficient of determination analysis, then partial hypothesis testing and simultaneous analysis. conducted with the help of SPSS 21 software. The results of this study show that the principal income of the regions influences the level of financial independence of the regions. The tax effort did not affect the financial independence of the regions. Capital expenditure has an impact on the region's level of financial independence. Region's own revenue, tax effort, and capital expenditures have a concurrent (together) impact on a region's degree of financial independence.